Impact of Food Quality, Price Fairness, and Authenticity on Customer Satisfaction and Behavior Intention - Leksana, Agista Putri; Arifin, Zainul; Sunarti, Sunarti; Bafadhal, Aniesa Samira (Wacana Journal of Social and Humanity Studies, 2025)
As the restaurant industry in Indonesia experiences rapid growth, consumer expectations for dining experiences are evolving. Diners are increasingly prioritizing authenticity, fair pricing, and high-quality food, all of which play crucial roles in enhancing satisfaction and encouraging repeat visits. This study examines the impact of authenticity, price fairness, and food quality on customer satisfaction and behavioral intentions. An explanatory research approach was employed, utilizing quantitative methods. The study was conducted at Griya Arayanna Restaurant, which features a Javanese-themed dining experience. The target population comprised visitors who had dined there at least once. Based on the Roscoe formula for sample selection, 150 participants were selected through purposive sampling. Data were analyzed using SEM PLS techniques. The findings indicate that authenticity, price fairness, and food quality have a significant impact on customer satisfaction and behavioral intentions. Moreover, satisfaction itself has a notable effect on behavioral intentions. At the same time, the factors of authenticity, price fairness, and food quality also exert an indirect influence on behavioral intentions through their impact on satisfaction. These insights suggest that restaurants should integrate cultural narratives into their promotional efforts, offering menu prices that appeal to a diverse customer base, and consistently uphold high food quality. Such strategies can enhance customer satisfaction, increase return visits, and lead to recommendations from others.Keywords: authenticity, behavioral intentions, food quality, price fairness, satisfaction